2011
DOI: 10.1111/j.1478-4408.2011.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the shade of an azo disperse dye on poly(ethylene terephthalate) and poly(lactic acid) fibres with its spectroscopic properties in selected organic solvents

Abstract: A series of azo disperse dyes was synthesised and the purified, synthesised dyes were characterised by proton nuclear magnetic resonance, thin-layer chromatography and melting point measurement. The spectroscopic properties of the dyes in solution were studied by dissolving the dyes in ethyl acetate and methyl benzoate. These were seen as mimicking the environment of the dye when inside dyed poly(lactic acid) and poly(ethylene terephthalate), respectively. Reflectance spectra of the dyes on both polyester subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This points out that the shade obtained on PLA differs from that on PET. It was reported that the shade difference was observed on PLA and PET when the two fibers were dyed at the same level of visual depth (Suesat et al, 2011). In addition, a brighter shade obtained on PLA was found (Choi & Seo, 2006;Blackburn, 2005).…”
Section: Study On the Spectroscopic Properties Of Disperse Dyes On Plmentioning
confidence: 84%
See 3 more Smart Citations
“…This points out that the shade obtained on PLA differs from that on PET. It was reported that the shade difference was observed on PLA and PET when the two fibers were dyed at the same level of visual depth (Suesat et al, 2011). In addition, a brighter shade obtained on PLA was found (Choi & Seo, 2006;Blackburn, 2005).…”
Section: Study On the Spectroscopic Properties Of Disperse Dyes On Plmentioning
confidence: 84%
“…from the solvatochromism study of disperse dyes mentioned in our previous work (Suesat et al, 2011). The light absorption capacity of the dye is influenced by polarity of the polymer medium.…”
Section: Dyeing and Build-up Properties Of Disperse Dyes On Pla Fibermentioning
confidence: 86%
See 2 more Smart Citations
“…The considerable biological and medicinal activities of nicotinic acid and its derivatives [2][3][4][5] have promoted recent interest in synthesis of new nicotinic acids of potential biological activities. Although condensation reactions of arylhydrazonals with active methylene nitriles were originally reported to afford pyridazin-6-imines [6], more recent studies have demonstrated that arylazonicotinates are also formed in some of these processes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%